Application of Lactobacillus gasseri 63 AM supernatant to Pseudomonas aeruginosa-infected wounds prevents sepsis in murine models of thermal injury and dorsal excision. Issue 10 (28th August 2019) - Lenzmeier, Taylor D.; Mudaliar, Nithya S.; Stanbro, Joshua A.; Watters, Chase; Ahmad, Aatiya; Simons, Mark P.; Ventolini, Gary; Zak, John C.; Colmer-Hamood, Jane A.; Hamood, Abdul N.
Abstract : Introduction. Severely burned patients are susceptible to bacterial infection within their burn wounds, which frequently leads to sepsis, multiple organ failure and death. The opportunistic pathogen Pseudomonas aeruginosa, an organism inherently resistant to multiple antibiotics, is a common cause of sepsis in these patients. Aim. Development of a topical treatment unrelated to conventional antibiotics is essential for prevention of P. aeruginosa infection and sepsis, leading to a role for the direct application of probiotics or their by-products. Methodology. We examined the effectiveness of 20× concentrated supernatant from Lactobacillus gasseri strain 63 AM (LgCS) grown in de Man, Rogosa and Sharpe broth in inhibiting P. aeruginosa biofilms in vitro, as well as in reducing wound bioburden and P. aeruginosa sepsis in vivo . Results. LgCS inhibited the growth of P. aeruginosa strain PAO1, prevented its biofilm development and eliminated partially developed PAO1 biofilms. In the murine model of thermal injury, a single injection of LgCS following injury and PAO1 infection reduced mortality to 0 % and prevented systemic spread (sepsis). Furthermore, a second injection of LgCS 24 h after the first eliminated PAO1 from the wound. In the murine dorsal excision infection model, either LgCS or ceftazidime treatment of the PAO1-infected wound significantly reduced the mortality rate among infected mice, while combining LgCS with ceftazidime eliminated mortality. Conclusion. These results suggest the potential of LgCS in preventing sepsis from P. aeruginosa infection in severely burned and other immunocompromised patients.